OC-074 Major improvement in the stage profile of tumours diagnosed in the NHS Bowel Cancer Screening Programme. (23rd September 2015) - Taylor, E F; Morris, E J A; Thomas, J D; Quirke, P; Forman, D; Coleman, M P; Rachet, B; Patnick, J
Abstract : Introduction: Regular screening has been shown to reduce the risk of dying from colorectal cancer by 16% and, in consequence, the NHS has established a new screening programme that aims to reduce mortality from this disease. This NHS Bowel Cancer Screening Programme (BCSP) collects detailed information about all screening participants. These data have been linked to the National Cancer Data Repository (NCDR)1 enabling tumours identified via the screening programme to be identified within a population-based data set of all the other colorectal tumours diagnosed in England. Methods: The NHS BCSP began in 2006 with a staged roll-out across England. The NCDR is currently complete up until the end of 2006 but will soon be extended to include tumours diagnosed in 2007. The current overlap between the two data sets allows an early snapshot of the benefits of the BCSP. Comparison of Dukes stage was performed in the screen detected and non-screen detected cancer populations. These analyses will be repeated on a larger data set once the 2007 tumours are available in the NCDR. Results: Comparison of the Dukes stage distribution of cancers from the screened and non-screened populations in the current data set demonstrates a significant stage shift. In the general population across all ages 93.2% of all colorectal cancer patients with Dukes A disease at diagnosis survive 5 years compared to 6.6% of Dukes D patients2 suggesting this stage shift will significantly improve outcomes. Conclusion: The introduction of the NHS BCSP has led to a significant stage shift between the non-screen and screen detected colorectal cancer populations. This study will go on to calculate the relative survival3 of the screen and non-screen detected colorectal cancer populations and use this information to calculate the number of premature deaths that could be avoided by the introduction of the NHS BCSP.